Академич Бадамын Лхамсүрэнгийн 90 насны ойд зориулсан эрдэм шинжилгээний хурал боллоо (Journal of International Studies, 2013)
English title: Research Meeting on Occation of the 90th Birthday of Badam Lkhamsuren Academician